Synthesis and characterization of vertically allgned ZnO nanowires by chemical vapor deposition for gas sensor applications - Chatchai Rodwihokช (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
In this work, vertically aligned ZnO nanowires were prepared on glass slide by chemical vapor deposition technique (CVD) in acetone ambient, assisted with seed layer. The seed layer prepared using zinc acetate dihydrate would be coated on substrate before set in tube furnace. The growth temperature and acetone flow rate were considered parameters in this research. ZnO nanowires were grown on substrate at various temperatures and acetone flow rates. The vertically aligned ZnO nanowires were characterized by X-ray diffractometry (XRD) and scanning electron microscopy (SEM) for crystal structure and well structure morphology with the diameter of aligned ZnO nanowires range from 150 to 400 nm. Then, the obtained vertically aligned ZnO nonawires were used to fabricate as ethanol sensors. Finally, their sensing properties are tested with 500 ppm of ethanol vapor. The ethanol sensors based on the vertically aligned ZnO nanowires reveal the high sensitivity at 500 celcius of operating temperature.